2008
DOI: 10.1089/jwh.2007.0450
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Child Abuse Victimization in Lesbian, Bisexual, and Heterosexual Women in the Nurses' Health Study II

Abstract: A growing body of research documents multiple health disparities by sexual orientation among women, yet little is known about the possible causes of these disparities. One underlying factor may be heightened risk for abuse victimization in childhood in lesbian and bisexual women. Using survey data from 63,028 women participating in the Nurses' Health Study II, we investigated sexual orientation group differences in emotional, physical, and sexual abuse in childhood and adolescence. Multivariable log-binomial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
116
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(123 citation statements)
references
References 47 publications
5
116
2
Order By: Relevance
“…One potential explanation is that sexual minority status may compromise economic stability, increasing women's likelihood of sex trade. Studies have also found that sexual minority women are more likely to have experienced adverse childhood experiences (e.g., childhood sexual abuse), 33,34 which are associated with sex trade. 35 Despite these potential hypotheses, causal mechanisms underpinning this finding are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…One potential explanation is that sexual minority status may compromise economic stability, increasing women's likelihood of sex trade. Studies have also found that sexual minority women are more likely to have experienced adverse childhood experiences (e.g., childhood sexual abuse), 33,34 which are associated with sex trade. 35 Despite these potential hypotheses, causal mechanisms underpinning this finding are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…This approach has not previously been used in research. Traditionally, in diverse types of studies, mostly heterosexual and mostly lesbian women have been placed into heterosexual or lesbian categories, respectively, comparing those two groups to bisexual women (Austin et al, 2007;Chivers et al, 2007;Kerr et al, 2013;King et al, 2008;McLaughlin et al, 2012).…”
Section: Included Variablesmentioning
confidence: 99%
“…Further, a meta-analysis investigating the link between female childhood sexual abuse and adult revictimization found that studies which used more inclusive definitions of childhood abuse yielded smaller effect sizes than studies with narrower definitions (Roodman and Clum, 2001). Further, it is possible that childhood abuse was not found to interact with mental health because the childhood abuse rates reported by the lesbian women may have been more similar to those reported by the non-monosexual than the heterosexual women (Austin et al, 2007). If the lesbian women included did in fact experience similar levels of childhood abuse as the nonmonosexual women, this could imply that our mediation analyses may have been compromised due to the previously documented link between childhood abuse, risky sex, and mental health.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study, lesbians with a BMI greater than 30 reported higher rates of lifetime sexual abuse (64%) than heterosexual women with similar BMIs (44%; Lehavot, Molina, & Simoni, 2012). Since several studies have found higher reports of childhood abuse, both sexual and other forms, among lesbian and bisexual women (Aaron & Hughes, 2007;Alvy, Hughes, Kristjanson, & Wilsnack, 2013;Austin et al, 2008;Balsam et al, 2005;Corliss et al, 2002;Stoddard et al, 2009;Wilsnack, Kristjanson, Hughes & Benson, 2012), this may be an important factor in the higher weight of sexual minority women. Some researchers have found child and adolescent abuse experiences to be linked to anti-gay beliefs of the perpetrators, particularly in women who are gender non-conforming (Alanko et al, 2009;D'Augelli et al, 2006).…”
Section: Effects Of Partners On Healthmentioning
confidence: 99%